Building Serverless Python Web Services with Zappa - Abdulwahid Abdulhaque Barguzar (Packt Publishing, 2018)
Dive into 'Building Serverless Python Web Services with Zappa' and master the art of developing scalable serverless applications in Python. This book gradually introduces you to AWS, serverless architecture, and the Zappa framework, and guides you through deploying web apps with Flask, Django, or Pyramid.What this Book will help me doLearn how to build, test, and deploy Python-based web services using the Zappa framework.Understand integration of serverless microservices with Amazon Web Services.Configure custom domains with SSL using AWS Route 53 and manage deployment configurations.Implement advanced Zappa settings for secure applications, including AWS VPC integration.Create a Docker container compatible with AWS Lambda environments.Author(s)None Barguzar is a seasoned software engineer with expertise in serverless development. With years of experience building scalable and efficient cloud applications, None shares practical, hands-on insights in this book to equip readers with actionable knowledge for their projects.Who is it for?The ideal readers of this book are Python developers eager to learn serverless application development using AWS and Zappa frameworks. Beginners looking for a structured introduction will find approachable explanations, while those with experience will benefit from its advanced techniques.